pintura realista en acrílico. - Arteaga Portilla, Mario Jordan (Machala: Universidad Tecnica de Machala, 2024)
The project titled "Movable Mural Painting as an Expressive Medium in Artistic Representation of the Problematic and Environmental Crisis Caused by Non-Renewable Energy Sources" aimed to create an artistic work that highlighted the social and environmental issues generated by the excessive use of non-renewable energies. Through a painting on a movable mural, it sought to sensitize the public and generate reflection on the need to adopt sustainable energy sources. The artwork was developed using acrylic painting techniques on a PVC canvas, chosen for its flexibility and lightness, which facilitated its transport and installation in different spaces. The mural's design reflected a contrast between an urban environment degraded by industrialization and the hope for a cleaner and more sustainable future, symbolized by bright and warm colors. To evaluate the impact of the work, it was promoted through social media, specifically on Facebook, where it was shared with family and friends. The post received a notable number of "likes," "shares," and comments, which allowed data to be collected on the perception and visual impact of the work. The comments reflected an appreciation of both the artistic technique and the conceptual message, showing that the mural successfully inspired significant reflection among viewers. The conclusions indicated that, although the artwork alone will not solve the energy crisis, it achieved its goal of generating discussion and awareness about the importance of renewable energies. The experience suggested that combining art and technology can be a powerful tool for education and social awareness. It was recommended to continue using art to address social and environmental issues, involving various communities and collaborating with experts in different disciplines to maximize the impact and effectiveness of the works. This project demonstrated that art can be more than just an aesthetic expression; it can be a catalyst for change and reflection in society, promoting a more conscious and sustainable future.
El proyecto titulado “La pintura en mural movible de obras como medio expresivo en la representación artística sobre la problemática y la crisis ambiental que causan las fuentes de energía no renovables” tuvo como objetivo principal crear una obra artística que evidenciara la problemática social y ambiental generada por el uso desmedido de energías no renovables. A través de una pintura en un mural movible, se buscó sensibilizar al público y generar una reflexión sobre la necesidad de adoptar fuentes de energía sostenibles. La obra se desarrolló utilizando técnicas de pintura acrílica sobre un lienzo de PVC, elegido por su flexibilidad y ligereza, lo cual facilitó su transporte e instalación en diferentes espacios. El diseño del mural reflejó un contraste entre un entorno urbano degradado por la industrialización y la esperanza de un futuro más limpio y sostenible, simbolizado por colores brillantes y cálidos. Para evaluar el impacto de la obra, se promovió a través de redes sociales, específicamente en Facebook, donde se compartió con familiares y amigos. La publicación recibió una notable cantidad de "me gusta", "compartidos" y comentarios, lo que permitió recopilar datos sobre la percepción y el impacto visual de la obra. Los comentarios reflejaron una apreciación tanto de la técnica artística como del mensaje conceptual, mostrando que el mural logró inspirar una reflexión significativa entre los espectadores. Las conclusiones indicaron que, aunque la obra por sí sola no resolverá la crisis energética, cumplió su objetivo de generar discusión y concienciación sobre la importancia de las energías renovables. La experiencia sugirió que la combinación de arte y tecnología puede ser una herramienta poderosa para la educación y sensibilización social. Se recomendó continuar utilizando el arte para abordar problemáticas sociales y ambientales, involucrando a diversas comunidades y colaborando con expertos en diferentes disciplinas para maximizar el impacto y la efectividad de las obras. Este proyecto demostró que el arte puede ser más que una simple expresión estética; puede ser un catalizador de cambio y reflexión en la sociedad, promoviendo un futuro más consciente y sostenible.
Keywords: ARTE; ENERGIA RENOVABLE; CRISIS AMBIENTAL; PINTURA ACRILICA; SENSIBILIZACION SOCIAL.